Rapid Binary Gage Function to Extract a Pulsed Signal Buried in Noise - Bagaria William J; Fahey Richard P; Garcia Sonia MF; Ratcliffe Colin (EURASIP Journal on Advances in Signal Processing, 2004)
The type of signal studied in this paper is a periodic pulse, with the pulse length short compared to the period, and the signal is buried in noise. If standard techniques such as the fast Fourier transform are used to study the signal, the data record needs to be very long. Additionally, there would be a very large number of calculations. The rapid binary gage function was developed to quickly determine the period of the signal, and the start time of the first pulse in the data. Once these two parameters are determined, the pulsed signal can be recovered using a standard data folding and adding technique.